2022
DOI: 10.3390/jcm11237226
|View full text |Cite
|
Sign up to set email alerts
|

Which Antibiotic for Urinary Tract Infections in Pregnancy? A Literature Review of International Guidelines

Abstract: Urinary tract infection (UTI) is considered to be a major problem in pregnant women. It is also one of the most prevalent infections during pregnancy, being diagnosed in as many as 50–60% of all gestations. Therefore, UTI treatment during pregnancy is extremely important and management guidelines have been published worldwide to assist physicians in selecting the right antibiotic for each patient, taking into account the maternal and fetal safety profile. A review of the literature was carried out and all inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…According to our findings, nitrofurantoin and amoxicillin-clavulanic acid should be recommended for use as an empirical therapy for UTIs in pregnant and nonpregnant women because bacteria have the least amount of resistance to these drugs, considering that nitrofurantoin should be avoided in the 3rd trimester of pregnancy [ 21 ]. On the other hand, bacteria had the greatest resistance to ampicillin, trimethoprim-sulfamethoxazole, and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, nitrofurantoin and amoxicillin-clavulanic acid should be recommended for use as an empirical therapy for UTIs in pregnant and nonpregnant women because bacteria have the least amount of resistance to these drugs, considering that nitrofurantoin should be avoided in the 3rd trimester of pregnancy [ 21 ]. On the other hand, bacteria had the greatest resistance to ampicillin, trimethoprim-sulfamethoxazole, and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, antimicrobial resistance for E. coli was lower in other studies, compared with our findings of 10.7% ESBL organisms, while GBS showed higher sensitivity to common antibiotics [ 32 , 33 ]. Regarding antibiotic use, most studies favor nitrofurantoin as the first-line treatment for UTIs in pregnant women, except for specific conditions and late pregnancy [ 34 ]. High organism sensitivity to penicillins, erythromycin, and cephalosporins is noted in the literature, with moderate sensitivity to cefuroxime, commonly used in empirical therapy for culture-negative cases, comparable to an overall resistance percentage of 12.1% for second-generation cephalosporines in our study, although it was significantly higher among mothers who gave birth preterm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current research is more concerned with the etiology, bacterial spectrum, and drug sensitivity of urinary tract infections in expectant women ( Belete, 2020 ; Belete and Saravanan, 2020 ; Getaneh et al, 2021 ; Ali et al, 2022 ). The guidelines for drug treatment regimens and follow-up after mode treatment for UTI in pregnancy are consistent, but there are still inconsistencies, such as prenatal screening for bacteriuria and the use of fluoroquinolones in lower or upper urinary tract infections ( Corrales et al, 2022 ). A study of 1,140 pregnant women with ASB revealed that it is impossible to determine which drug is the most effective or safe for treating UTIs during pregnancy ( Guinto et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%